Freshwater Foraminifera Biodiversity in New England (USA): Evaluation of Field Sites and a Botanical Garden - Adri K. Grow; Laura A. Katz (Ecology and Evolution, 2025)
ABSTRACT Despite textbook definitions of foraminifera as marine organisms, foraminifera also occur in freshwater habitats, with first reports from ~150 years ago. Yet, to date, very few freshwater foraminifera have been described in part because these fragile organisms are rarely cultivable. There are fewer than 20 freshwater foraminifera species described both morphologically and molecularly, and a preliminary genome analysis has been done for only one species (Reticulomyxa filosa). In this study, we use foraminifera‐specific primers designed to amplify a portion of the 18S rRNA gene as a means of characterizing freshwater foraminifera community diversity from both field sites and a botanical garden. Our focus is on exploring trends in freshwater foraminifera composition in low‐pH bogs, carnivorous pitcher plants, and a greenhouse environment, with all sites sampled in Massachusetts and Maine (USA). Our preliminary results highlight the low diversity of freshwater foraminifera in these environments, which is in striking contrast to the tremendous diversity found among marine lineages. We also find lineages (i.e., operational taxonomic units [OTUs]) that are widespread and others that appear to be site‐specific, and we identify several clades of “unknown” freshwater foraminifera (i.e., those lacking previous molecular identification) that may be specific to the sampled locations. Together, these data help to expand our understanding of freshwater foraminifera biogeography through analyses of extreme habitats such as low‐pH bogs and fens.